2005
DOI: 10.1177/153331750502000407
|View full text |Cite
|
Sign up to set email alerts
|

Tube feeding, antibiotics, and hospitalization of nursing home residents with end-stage dementia: Perceptions of key medical decision-makers

Abstract: This article discusses the literature supporting the limited use of tube feeding, antibiotics, and hospital transfers of nursing home residents with end-stage dementia. This article also presents the findings of a study that queried 138 nursing home social service staff members in New York State regarding positions taken by key medical decision makers regarding tube feeding, antibiotic use, and hospitalization of nursing home residents with end-stage dementia. Results are discussed in the context of positions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…33 The goal of prolonging life is considered inconsistent with the palliative philosophy, and it is even less appropriate in cases of advanced dementia. 7 Nonetheless, these findings confirm the existence of a gap between the recommendations of palliative care philosophy and the positions of doctors 34 and nurses, 35 who seem, at least in Italy, culturally more inclined to prolong life and thus to favor the administration of antibiotics.…”
Section: Typology Of Critical Decisionsmentioning
confidence: 68%
“…33 The goal of prolonging life is considered inconsistent with the palliative philosophy, and it is even less appropriate in cases of advanced dementia. 7 Nonetheless, these findings confirm the existence of a gap between the recommendations of palliative care philosophy and the positions of doctors 34 and nurses, 35 who seem, at least in Italy, culturally more inclined to prolong life and thus to favor the administration of antibiotics.…”
Section: Typology Of Critical Decisionsmentioning
confidence: 68%
“…This varied greatly from doctors and relatives, to speech and language therapists, dieticians and multidisciplinary teams. Of studies which collected data on who had the most influential role in the decision-making process, 14 studies found one or more of the physicians to be the most influential [35], [36], [42], [44], [49], [52], [57], [58], [61], [65], [71], [74], [84], [94], nine found collaborative decision-making between the relatives or substitute decision-makers and members of the medical team [46], [50], [51], [65], [73], [86], [90], [95], [96], three studies found that the relative or surrogate decision-maker were the most influential or felt they had the final say [41], [59], [97], and one study found that the medical director was the most influential [98]. However, the real-life picture may be more complex than these findings indicate, as one study reveals that although surrogate decision-makers authorised the decision in 92.2% of the cases, a detailed discussion with the patient or surrogate was only documented in one of the 154 cases [59].…”
Section: Resultsmentioning
confidence: 99%
“…Very few studies have engaged with how carers interact with professionals in the decision-making process, nor have they described what is required for effective communication (Caron et al, 2005b) even though it is clear that how physicians resolve and negotiate patient and family preferences regarding care appears to directly influence patient outcomes (Helton et al, 2006). In the absence of agreed guidelines, and advance care plans, decision making for people with dementia at the end of life is shaped by differences in religious beliefs, professional training, understanding of the disease, what is meant by palliative care, perspectives of other patients, culture and beliefs (Luchins and Hanrahan, 1993;Cavalieri et al, 2002;Hinkka et al, 2002;The Anne Mei, 2002;Lacey, 2005;Haydar et al, 2004;Rurup et al, 2006). Despite discussion and exploration of the feasibility of introducing advance care planning into long term care for people with dementia , we found no studies that evaluated the impact of advanced care directives on the overall approach to end-of-life care and its related outcomes of place of death, treatments received and carer involvement in and satisfaction with the home or care home environment.…”
Section: Decision Making At the End Of Lifementioning
confidence: 99%